A methods engineering study on Laura's Food Corporation - Fortunato, Sheryl (College of Engineering, 2005)
The study aims to pinpoint the problematic areas in the hard dough production process and be able to arrive at necessary, practical and economical recommendations for improvement. These proposed solutions intend to increase productivity and/or standardize existing processes and procedures. A systematic and thorough examination of the production line, mostly video recording, ensures the precision of the data obtained. Video documentations are treated with utmost confidentiality, in keeping with the management's desire to protect company "trade secrets." Analysis tools such as the Stream Diagnostic and Pareto Chart, Kepner-Tregoe are employed in order to identify the sources of the main problems and have an effective means of weighing the alternatives, thereby arriving at the optimal and feasible course of action. Problematic areas which the study focused on include, poor working conditions, insufficient work standards and control measures, poor materials handling and inefficient layout. There is much room for improvement with regards to standardizing production methods. Adapting and implementing stricter work standards would decrease the product wastage and make for a more efficient production line. The flow of material and employees in the plant floor adds to the inefficiency of production because of backtracking in movement and material transfer. Two alternative plant layouts are presented in the study. Minimizing worker and material movement on the plant floor and easy accessibility of key points in the production process were main consideration in the formulation of the proposed plant layouts. Overall results of the implementation of the proposed alternative would be, increased product output and standardization of current practices and procedures. Such outcomes would coincide with the company's present venture into the international market.